Badan Eksekutif Mahasiswa sebagai Laboratorium Kepemimpinan Islami: Peranannya dalam Meningkatkan Motivasi Belajar di Perguruan Tinggi Islam - Novrizal, Nesa; Rokimin, Rokimin; Fauzi, Anas (Universitas KH. A. Wahab Hasbullah, 2025)
This study stems from concerns that the role of student organizations, particularly the Student Executive Board (BEM), is often perceived as limited to non-academic activities, when in fact it can serve as a driving force for learning motivation. This study aims to understand how the BEM at Darunnajah University acts not only as a forum for student activities, but also as a catalyst that fosters academic enthusiasm while honing leadership and personal development skills. This study uses a qualitative approach through in-depth interviews with student affairs staff, BEM administrators, and active students. Interestingly, the analysis results produced four interrelated themes. First, BEM functions as a catalyst for learning motivation through academic programs such as seminars, workshops, scientific discussions, and writing competitions, which have been proven to foster students' confidence and enthusiasm for learning. Second, the program design strategy has proven to be adaptive because it is based on needs surveys, aspiration forums, and faculty collaboration, so that the program is not merely ceremonial. Third, institutional support in the form of funding, facilities, and faculty guidance is an important pillar, although challenges such as conflicting class schedules, low participation, and leadership regeneration issues remain obstacles. Fourth, involvement in BEM has a broad impact, ranging from strengthening learning motivation to improving soft skills, time management, and readiness for the world of work. Thus, this study confirms that student organizations can be viewed as laboratories for Islamic leadership that integrate academic, social, and spiritual aspects. The implication is that universities need to strengthen institutional support and encourage broader student involvement. In the future, similar studies should focus on external collaboration models so that BEM's contribution to student motivation and career development can be optimized.